XVI Color Conference (diségno, 2020)
For many years the Color Group has been promoting theoretical and practical sector research, with an increasingly interdisciplinary outlook. The organization, founded in 2004, but which traced its roots back to 1995, has always fulfilled the tasks it had set itself during the drafting of the statute: a) promote the study of color in all its aspects, including aspects relating to vision; b) offer the various people and / or groups of people who have to do with color in its various aspects, scientific, industrial, aesthetic or didactic, the opportunity to meet and communicate their problems; c) launch the necessary or desirable activity to raise a representative opinion on the various problems of standardization, specification, nomenclature and all other aspects that the Group will consider necessary to assist the research; d) encourage and promote the investigation of color phenomena and color measurement and the attempt to ensure that Italy is aware of the developments taking place in other countries of the world; e) assist in the dissemination of knowledge of color (read more).